Review on Ceramic Disc Brake System - Manavalan, S.; Gopi, Aswin; Arivarasu, J.; Abishek Ahi, A.; Chandru, S. (International Journal of Psychosocial Rehabilitation, 2019)
Braking is a method that converts the mechanical energy of the vehicle into mechanical energy that should be dissipated in the form of heat. While not breaking within the vehicle can place a rider in an unsafe position. Brakes convert friction to heat; however, if the brakes get too hot, they’re going to stop to figure as a result of they can’t dissipate enough heat. Therefore, researches occur during this field for decreasing the temperature result, so by this we are able to operate simply. Several new materials were introduced for the disc brake rotor to resist warm temperatures made throughout braking action. With the exception of the warm temperature property, the disc rotor materials should even have high thermal physical phenomenon property, as this property decides the number of warmth dissipation to the air stream from the disk rotor. Within the gift work, a gray forged iron material and metal-ceramic have been chosen for the disc brake rotor. To conclude the temperature history for the gray forged iron material and metal-ceramic, a numerical simulation technique known as the finite technique is employed. Transient analysis is applied in ANSYS to predict temperature distribution as an operation of your time within the disc brake rotor. The results from the transient analysis area unit were compared. It’s necessary to try and do the structural analysis when performing thermal analysis in ANSYS to review the steadiness and rigidity behavior of the rotor material. The results obtained by finite component simulation and smart material are urged